Sejarah erupsi Gunung Bromo 1995: kajian dampak dan upaya mitigasinya di Kecamatan Sukapura - Hasna Fauziah Noorsy; Blasius Suprapta; Ronal Ridhoi (Historiography: Journal of Indonesian History and Education, 2022)
Environmental history has recently become a popular topic. Environmental history, on the other contrary, is still a neglected historical specialization in Indonesia. Environmental history, including past natural disasters, is an interesting topic to study. Volcanic eruptions are a natural occurrence that has received little attention by researchers. Mount Bromo's eruption in 1995 became a historical event that historians should research and reconstruct.In 1995, it lasted for several months, with increasing volcanic activity that continues to occur, causing environmental and social impacts. Mount Bromo, which is included of the Bromo Tengger Semeru National Park's conservation area, contributes to the tourism aspect. To deal with all of the risks that occurred during the 1995 eruption of Mount Bromo, the government, the Great Hall of Bromo Tengger Semeru, and the local community made mitigation efforts. This research uses the historical method, which entails a thorough examination of archival sources, newspapers, articles, books, maps, and interviews with relevant parties. The facts about Mount Bromo's 1995 eruption, including its ecological impacts and mitigation efforts, are presented in this study.